Implementation of the Sight Words Method to Improve Word Reading Skills in Sixth-Grade Students with Autism Spectrum Disorder - Erisa Eka Nur Cahyani; Nur Azizah (Universitas Negeri Malang, 2025)
Abstract: This research aims to improve the ability to read words through the sight words method for student with autism in grade VI at the Dian Amanah Special School. This research is a Classroom Action Research with the Kemmis and Mc. Taggart model, consisting of two cycles. The subject was one sixth-grade student. Data collection using test and observations of learning behavior. Hypothesis testing was carried out by comparing the scores of student learning outcomes in the pre-action test, post-action test in cycle I, and post-action test in cycle II. The results showed that the sight words method was able to improve the ability to read words for student with autism in grade VI, as evidenced by an increase in the score of the learning outcome test for the ability to read words from 40 in the pre-action test, to 73 in the post-action test in cycle I, and to 89 in the post-action test in cycle II. The improvement in student learning behavior, such as increased focus in learning, the ability to identify words, the ability to read words, and the ability to read words in sentences with SPOK patterns sequentially. Abstrak: Penelitian ini dilakukan untuk meningkatkan kemampuan membaca kata melalui metode sight words bagi peserta didik autis kelas VI di Sekolah Luar Biasa Autisma Dian Amanah. Penelitian ini merupakan Penelitian Tindakan Kelas dengan model Kemmis dan Mc. Taggart, yang dilaksanakan sebanyak 2 siklus. Subjek dalam penelitian ini adalah peserta didik autis kelas VI SLB. Data dikumpulkan dari tes hasil belajar dan observasi perilaku belajar. Analisis menggunakan deskriptif kuantitatif. Data disajikan dalam bentuk tabel dan diagram. Pengujian hipotesis dilakukan dengan membandingkan skor hasil belajar peserta didik pada tes pra tindakan, tes pasca tindakan pada siklus I, dan tes pasca tindakan pada siklus II. Hasil penelitian menunjukkan metode sight words mampu meningkatkan kemampuan membaca kata bagi peserta didik autis kelas VI di SLB Autisma Dian Amanah, yang dibuktikan adanya peningkatan skor tes hasil belajar kemampuan membaca kata dari 40 pada tes pra tindakan, menjadi 73 pada tes pasca tindakan siklus I, dan menjadi 89 pada tes pasca tindakan siklus II. Adapun peningkatan perilaku belajar peserta didik, seperti meningkatnya fokus dalam pembelajaran, kemampuan mengidentifikasi kata, kemampuan membaca kata, dan kemampuan membaca kata dalam kalimat berpola SPOK secara runtut.